UJI IRITASI SEDIAAN STICK TABIR SURYA EKSTRAK BUNGA TELANG (Clitoria ternatea (L.)) DAN PEGAGAN (Centella asiatica (L.)) - Komaliya, Risyda; Audina, Mia (Universitas Tribhuwana Tunggadewi, 2024)
Butterfly pea flowers (Clitoria ternatea (L.)) and gotu kola (Centella asiatica (L.)) contain phenolic compounds. The phenolic compounds in butterfly pea flowers are anthocyanins, while in gotu kola, there are flavonoids and tannins. Butterfly flower extract and gotu kola extract have certain concentrations of SPF values in the maximum category. This research aimed to determine the results of the irritation test of sunscreen stick preparations of butterfly pea flower extract (Clitoria ternatea (L.)) and gotu kola (Centella Asiatica (L.)). This research uses an experimental approach with a true experimental design. Stick preparations are divided into formulations with a combination of active ingredients of butterfly pea flower (Clitoria ternatea (L.)) at a concentration of 2% or 3%, and gotu kola extract (Centella asiatica (L.)) at a concentration of 7% or 8%. The optimal formulation of the preparation is adjusted to the evaluation results and specified requirements. The research showed that sunscreen sticks with two different formulations were applied to the skin 2.5 cm wide and then left for 1 hour to determine whether the skin began to show signs of irritation, such as redness, swelling, or itching. This irritation test was carried out on 20 volunteers, then observed for 3 days, and showed that the formulation of 2 sunscreen stick preparations did not irritate